Peak stress relief of cross folding origami - Ma, J; Hou, D; Chen, Y; You, Z (Elsevier, 2017)
In this paper, cross folding of an elastic sheet, a common folding method in packaging a deployable antenna reflective membrane, was studied numerically with the aim of eliminating material failure in the sheet. The deformation, stress distribution, and peak stress of the sheet, as well as the effects of geometrical parameters on those properties were systematically investigated. Then two methods, i.e., central hole method and central slit method, were explored to reduce the peak stress caused by cross folding. A central slit parallel to the first folded crease was found to be most effective in reducing the peak stress.